PENGARUH PENGANGGARAN PARTISIPASI, PERENCANAAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PENYUSUN ANGGARAN ( STUDI KASUS PADA RSUD RAA SOEWONDO PATI ) - Karyadi, Agus; Sunarto, Sunarto (Jurnal Ilmiah Telaah Manajemen, 2014)
The present study aims to examine the effect of budgetary participation, budgetary planning and organizational commitment to performance budgeting. Collicting data this study used a questionnaire sutvey. The questionnaire submitted to 62 employees involvedin the preparation of the Business Plan and Budget, a total of 60 completed questionnaires were returned and processed. Data analysis was performed using regression analysis The analysis result indicate that participation budgeting significant positive effect on performance budgeting, budget planning significant positive effect on performance budgeting, and organizational commitment also significant positive on performance budgeting. Keywords: participation, planning, commitment, and performance